Metastatic renal cell carcinoma of the pancreas mimicking neuroendocrine tumor diagnosed by endoscopic ultrasound‐guided needle biopsy. Issue 9 (21st September 2021) - De Luca, Luca; Tommasoni, Silvia; Mangiavillano, Benedetto; Repici, Alessandro
Abstract: Pancreatic metastases of kidney are rare, and they can occur several years after nephrectomy. EUS‐guided histology needle and appropriate immunohistochemistry stains are pivotal in showing pathognomonic marker of clear cell renal cell carcinoma. Abstract : Pancreatic metastases of kidney are rare, and they can occur several years after nephrectomy. EUS‐guided histology needle and appropriate immunohistochemistry stains are pivotal in showing pathognomonic marker of clear cell renal cell carcinoma.